Reclaiming “a dark and malefic sacred” for a Theology of Disability - Metzger, James A. (Journal of religion, disability & health, 2011)
As theological inquiry on disability has evolved over the past two decades, broad agreement appears to be emerging in four areas: 1) preferred model of disability; 2) epistemological standpoint; 3) overall assessment of biblical and theological traditions; and 4) constructions of God (when God is spoken of at all). After addressing each of these four areas, the author explores a growing edge in the dialogue, namely, how sustained reflection on ambivalent or aversive experiences of disability might be brought to bear on our constructions of deity. For persons who at times have experienced the body not as companionable friend but as unrecognizable foe, contemporary constructions of God as just, loving, and compassionate, now ubiquitous in traditional and progressive Christian communities alike, may seem unpersuasive. For such persons, it is suggested that a reclamation of biblical and theological traditions that testify to an experience of the sacred as indifferent or oppressive may not only resonate but prove beneficial as well.